Leucine elicits myotube hypertrophy and enhances maximal contractile force in tissue engineered skeletal muscle in vitro. Issue 10 (8th May 2017) - Martin, Neil R.W.; Turner, Mark C.; Farrington, Robert; Player, Darren J.; Lewis, Mark P.
Abstract : The amino acid leucine is thought to be important for skeletal muscle growth by virtue of its ability to acutely activate mTORC1 and enhance muscle protein synthesis, yet little data exist regarding its impact on skeletal muscle size and its ability to produce force. We utilized a tissue engineering approach in order to test whether supplementing culture medium with leucine could enhance mTORC1 signaling, myotube growth, and muscle function. Phosphorylation of the mTORC1 target proteins 4EBP‐1 and rpS6 and myotube hypertrophy appeared to occur in a dose dependent manner, with 5 and 20 mM of leucine inducing similar effects, which were greater than those seen with 1 mM. Maximal contractile force was also elevated with leucine supplementation; however, although this did not appear to be enhanced with increasing leucine doses, this effect was completely ablated by co‐incubation with the mTOR inhibitor rapamycin, showing that the augmented force production in the presence of leucine was mTOR sensitive. Finally, by using electrical stimulation to induce chronic (24 hr) contraction of engineered skeletal muscle constructs, we were able to show that the effects of leucine and muscle contraction are additive, since the two stimuli had cumulative effects on maximal contractile force production. These results extend our current knowledge of the efficacy of leucine as an anabolic nutritional aid showing for the first time that leucine supplementation may augment skeletal muscle functional capacity, and furthermore validates the use of engineered skeletal muscle for highly‐controlled investigations into nutritional regulation of muscle physiology. Abstract : The effect of the amino acid leucine on myotube size and muscle force production were tested in engineered skeletal muscle in vitro. Leucine activated mTORC1 signaling and augmented contractile force, effects which were completely blunted by co‐incubation with rapamycin. Chronic contractions (24 hr) alongside leucine treatment further increased muscle force, but not myotube size. This data provides further evidence of the efficacy of leucine in regulating muscle size and function, and may prove a useful strategy to improve the therapeutic potential of engineered skeletal muscle.